Faktor-Faktor Yang Mempengaruhi Kinerja Pegawai Bpkad Kabupaten Bengkulu Selatan - Neti Herlianti; Karona Cahaya Susena; Yudi Irawan (Jurnal Fokus Manajemen, 2023)
The type of research used in this research is qualitative research with a descriptive approach. The population in this study is all State Civil Servants (ASN) at the Regional Financial and Asset Management Agency of South Bengkulu Regency, totaling 40 ASN. The results of the multiple linear regression analysis are Y = 6.856 + 0.519 X1 + 0.340 X2, this illustrates a positive regression direction, meaning that the variable work ability (X1) and work discipline (X2) have a positive influence on employee performance (Y) in the BPKAD service South Bengkulu Regency. The magnitude of the coefficient of determination from the calculation results using SPSS can be seen that the coefficient of determination from R square is 0.757. This means that the value of work ability (X1) and the value of work discipline (X2) has a significant effect on employee performance (Y) of 75.7% while the remaining 24.3% is influenced by other variables not examined in research. The results of the t test at level a significance of 0.05 explains that partially work ability and work discipline have a significant influence on employee performance in BPKAD South Bengkulu Regency. It can be seen that the significance value of work ability and work discipline is less than 0.05.